EFFECT OF BIO HEALTH, TECAMIN MAX AND BENZYL ADENINE ON GROWTH CHARACTERISTICS OF SWEET ORANGE SEEDLINGS - A. S. Abdulrhman; Sh. M. M. Al-Atrushy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This investigation was aimed to study the effect of soil application of Bio health and foliar application with Tecamin max and Benzyl adenine on growth characteristic of sweet orange (Citrus sinensis L.) seedlings during two successive seasons (2020 and 2021). Bio health was added with three concentrations (0, 6 and 12 g.L-1) to the soil and foliar application of Tecamin max with three concentration (0, 5 and 10 ml.L-1), Benzyl adenine with three concentration (0, 100 and 200 mg. L-1) on the sweet orange seedlings which were brought from private nursery in Duhok city and have two- years old and nearly uniform in growth vigor. The results proved that all parameters such as increases in plant high, stem diameter, branch numbers, single leaf area, total chlorophyll as soon as leaves carbohydrate and leaves dry weight in both seasons were increased significantly as compared with control, accept Tecamin max had no significant effect on leaves carbohydrates and leaves dry weight, Benzyl adenine no significant effect on leaves dry weight on both seasons, Furthermore, combination among high concentration of Bio health, Tecamin max and Benzyl adenine improved all parameters in comparison with the control.